Effect of group hope therapy on self-efficacy of adolescents with type 1 diabetes - Esfahani,Nasim Nikbakhtan (2021)
SUMMARY OBJECTIVE: This study aims to determine the effect of group hope therapy on the self-efficacy of adolescents with type 1 diabetes. METHODS: This randomized clinical trial was conducted on 45 adolescent patients with type 1 diabetes in Iran. The subjects were randomly assigned into the intervention and control groups. The intervention group received eight 90-min sessions of group hope therapy using Snyder's method. RESULTS: The mean score of self-efficacies in the intervention group was significantly higher than the control group (p<0.05). CONCLUSION: The results of the study suggested that group hope therapy had a significant impact on self-efficacy of adolescents with type 1 diabetes but had no effect on academic self-efficacy and self-efficacy in blood glucose management.